PERMASALAHAN TEKNIS INSTALASI PENGOLAHAN AIR LIMBAH PABRIK MINYAK KELAPA SAWIT - Rahardjo, Petrus Nugro (Center for Environmental Technology, 2005)
Crude palm oil produced in Indonesia has already been known as the second largest in Asia. Unfortunately tens of palm oil factories (CPOF) spread out in Indonesia have not good wastewater treatment plants (WWTP) yet. PT. Kertajaya, as an example, which is located in Regency Pandeglang, still has BOD contained in its final effluent of the wastewater treatment plant more than 200 ppm. In fact the capacity and capability of WWTP in PT. Kertajaya are much more than enough for only 288 m3 per day. Because of improper operation and maintenance of the WWTP, the technical problems are accumulated, such as, increasing the sediment, decreasing the retention time and channelling of the wastewater being treated. The following affect is the treatment process is not going well and the quality of effluent is getting worse. To solve the technical problems, it is very important to remove the sediment periodically and give aeration in the aerobic pond. A recommendation for the wastewater treatment system has been proposed. The system has eight processes including oil separation or first sedimentation, neutralization, equalization, anaerobic degradation, aerobic degradation,Ã‚Â final sedimentation and sludge drying.Ã‚Â Katakunci : BOD, technical problem, wastewater, anaerobic. Aerobic process